Using a Task Analysis Process for Reading and Writing Assignments. - Philippakos, Zoi A. (Reading Teacher)
Abstract: Proficient writers spend substantial time planning for writing, and that planning begins with analyzing the writing task. They spend time considering the topic, the audience and its needs, and the genre and form of the writing. This rhetorical analysis helps them set goals, orient their attention, and get organized. Task analysis can also help students navigate reading tasks and challenging combined reading–writing tasks. This teaching tip explains a process for critically reading and analyzing writing tasks, as well as combined reading–writing tasks, that can be immediately applied in teachers’ classrooms.